Вы находитесь на странице: 1из 107

1

f(t)

0
T







, ,




f(t)

:
f (t ) = A 0 +

=1

=1

B sin t + C cos t =

= A0 +

Am sin(t + )

=1

1
A 0 = f (t )dt
T0

-
7

2
B = f (t ) sin(t ) dt
T0

-
-
8

2
C = f (t ) cos(t ) dt
T0

-
-
9

Am =

2
B

2
+

-
-
10

C
= ( 180) + arctg

- ,
180
Bk<0
11

= 1,2,3...

12

2 1
= 2f = ,
T c

-
()
13

14

f(t)


,
f(t)

,


15

f(t)



,

16


f (t ) = A 0 + A m1 sin( t + 1 ) +
+ A m 2 sin( 2t + 2 ) + A m 3 sin( 3t + 3 ) +
+ A m 4 sin( 4t + 4 )

17

)
m

m1

m2
m3

m4

18

90

1
2
1

3
19


u(t ) = 1 + 2 sin t + 1 sin( 2t + 90 ), B

U0 = 1 B
U m1 = 2 B

1 = 0
2 = 90

Um 2 = 1 B

20

B
3

u(t)

u ( t ) = U 0 + u1 + u 2

U0

u2

0
-1

u1 t

-2
-3

T = 2

21

22

f ( t ) = A 0 + A m1 sin( t + 1 ) +

+ A m 2 sin( 2t + 2 ) + ...

23

1.
T

1
A 0 = f ( t )dt
T0

-
24

2.
T

1
= f (t ) dt
T0

25

3.
Am

-
f(t)

26

f(t)

Am
f(t)

27

4.
A

-
f(t)

28

2
A m1

2
Am 2

1 2
2
A=
f ( t ) dt = A 0 +
+ ... =
+

T0
2
2

2
A0

2
+ A1

2
+ A2

+ ...

29


A m1
Am 2
A1 =
, A2 =
...
2
2

-

30

:
i( t ) = 6 + 8 2 sin( t + 30) +
+ 7.07 sin( 3 t 60), A
2

7.07
I= 6 +8 +
= 11.18 A
2
2

31

u( t ) = 3 + 4 2 sin( t + 90), B

U= 3 +4 =5B
2

32

(I)
(U)

R:
2

U
,
P=I R=
R
2

33

34

1.



:

35

36

2.

37

3.


38

4.

( )

39

40

41

1.

= 1,11
42

2.

m
=
A

= 2 = 1,41
43

3.
1 m1
=
=

2A

= 1
44

4. ( 0 = 0)
=

2
2

2
+ 3

+ ...

= 0
45



:
0,05

46

47

i(t )
u( t )

48

u(t ) = U 0 + 2U1 sin( t + 1 ) +


+ 2U 2 sin( 2t + 2 ) + ...

i(t ) = I 0 + 2I1 sin( t + 1 ) +


+ 2I 2 sin( 2t + 2 ) + ...
49

1.

W = P t = P n T,

n = 1, 2, 3...

2
T=

50

P = P0 + P1 + P2 + ... = U 0I 0 +
+ U1I1 cos 1 + U 2I 2 cos 2 + ... ,

1 = 1 1
2 = 2 2
51

52

2. Q
( ):
Q = Q1 + Q 2 + ... =

= U1I1 sin 1 + U 2I 2 sin 2 + ... ,

53

3. S
( ):
S = UI =

2
I0

2
U0
2
+ I1

2
+ U1
2
+ I2

2
+ U2

+ ...

+ ... ,

54

S P +Q
2




( )
55

T = S P Q
2

,

.
, .

S = P +Q
2

T = 0
56

f(t)

u( t )
i(t )
0

57

4.
P
cos = 1
S
P

= arccos
S
58




,
,
,

,

.
59


u(t ) = 2U sin( t + 1 )
i(t ) = 2I sin( t + 1 )
: U =

I=

2
2
U 0 + U1 + U 2 + K
2
2
2
I 0 + I1 + I 2 + K
2

60


i( t )

u(t ) = U 0 + 2U1 sin( t + 1 ) +


+ 2U 2 sin( 2t + 2 ) + K

u( t )
u( t ) U o
U1
i( t ) =
=
+ 2
sin( t + 1 ) =
R
R
R
U2
+ 2
sin( 2t + 2 ) + K
R

61


k-

Uk
Ik =
R

1 = 2 = K = 0

P = U 0I 0 + U1I1 cos 1 + U 2I 2 cos 2 +


+ ... =

2
I0R

2
I1 R

2
I 2R

+ K = I R ,
2

62

P = I R , B
2

I=

2
I0

2
I1

2
I2

+K

63

Q = U1I1 sin 1 + U 2I 2 sin 2


+K= 0

1 = 2 = K = 0

64

S = UI = I R , BA
2

T = S P = 0
2



65

xL
i ( t ) u( t )

i(t ) = I 0 + 2I1 sin( t + 1 ) +


+ 2I 2 sin( 2t + 2 ) + K
66


di(t )
u( t ) = L
= 2LI1 cos(t + 1 ) +
dt
+ 2 2LI 2 cos( 2t + 2 ) + K =
= 2U1 sin( t + 1 + 90 ) +
0

+ 2U 2 sin( 2t + 2 + 90 ) + K
0

67

k-

Uk =
(k )
xL

(k )
I k xL ,

(1)
kxL

= kL,
68

k
xL - k-
;

(1) -
xL

69



U 0 = 0 ,

.

70

P = U 0I 0 + U1I1 cos 1 + K = 0

1 = 2 = K = 90

Q = U 1 I 1 sin 1 + U 2 I 2 sin 2 +
+K> 0
71

S = UI, BA

T = S Q 0
2

72



(k )
xL

(1)
kxL

= kL,

Uk
Ik = (k )
xL
73

xC
i( t )

u( t )

u(t ) = U 0 + 2U1 sin( t + 1 ) +


+ 2U 2 sin( 2t + 2 ) + K
74

du(t )
i( t ) = C
= 2CU1 cos(t + 1 ) +
dt
+ 2 2CU 2 cos( 2t + 2 ) + K =
= 2I1 sin( t + 1 + 90 ) +
0

+ 2I 2 sin( 2t + 2 + 90 ) + K
0

75

k-

Uk
Ik = (k ) ,
xC
(k )
xC

(1)
xC

1
=
=
,
k
kC
76

( k ) - k-
xC

(1 ) -
xC

77


I 0 = 0 ,

.

78

P = U 0I 0 + U1I1 cos 1 + K = 0

1 = 2 = K = 90

Q = U 1 I 1 sin 1 + U 2 I 2 sin 2 +
+K< 0
79

S = UI, BA

T = S Q 0
2

80

,
,
k-

k- ,
, ..
.

Uk
I k = ( k ) = Uk kC
xC
81

82






, ..




83

R=const :
(k )
xL

= kxL = kL

(k )
x

x
1
=
=
k kC

(k )
x

= kx = k
84

R
e(t )

J(t )

uC (t )
i L (t )

85

:
e(t ) = E0 + 2E1 sin( t + 1 )
J (t ) = J 0 + 2J 2 sin( 2t + 2 )

, R , L, C
86

i L (t ) , uC (t )
87

1.
(=0)

88

J0
U C0

I L0

89

I L0 = J 0
U C0 = E0 I L 0 R = E0 + J 0 R

90

2.
(=1)

91

jxL

R
&
E
1

jxC
I& L1

&
U
C1

92

1
& = E e ; xC =
; x L = L
E
1
1
C
&1
E
j
&I L1 =
= I L1e , A
R + jxL jxC
j1

j
&
&
U C1 = I L1 ( jxC ) = U C1e , B
1

93

3.
(=2)

94

j2xL
R

jxC
I& L 2

J& 2
&
U
C2

95

&J = J e j2
2
2
jxC
I& L 2 = J& 2

R + j2xL j

xC

= I L 2e

j 2

,A

2
96

& C2
U

jxC
( R + j2xL )

&
= J2
=
jxC
R + j2x L
2
= U C 2e

j 2

,B
97


i L (t ) = J 0 + 2I L1 sin( t + 1 ) +

+ 2I L 2 sin( 2t + 2 ), A
uC (t ) = U C0 + 2U C1 sin( t + 1 ) +

+ 2U C 2 sin( 2t + 2 ),
98

99

100





()
0
-

,

101




()


.



102

1:

u1 (t ) = U 0 + 2U1 sin( t + 1 )

u 2 (t ) = 2U1 sin( t + 1 )
103

1
u1 ( t )

2
u 2 (t )
'

'

j
=

= jL
=0
C
- 1
(1)
Z12

(1)
jxL

(1)
jxC

104

2:

u1 (t ) = U 0 + 2U1 sin( t + 1 )

u 2 (t ) = U 0
105

2
C

u1 ( t )

u 2 (t )

'

(1)
Z12

(1)
(1)
jxL [ jxC ]
(1)
(1)
jxL jxC

'

- 1
106

:
1. .., . .- .:
, 2003,
. 120-125.
2. .
.1: / . ..
. - .: , 1996, . 200213.
3. .., .. .-:
, 1989, . 200-217.
4. .. .
.-: - , 2006, .
54-61.
107